Crumbling Walls, Crumbling Roles: Metatheatricality and Gender Performativity in Héctor Mendoza's La dama boba (1981). Issue 1 (2nd January 2020) - Meredith, Dana A.
Abstract: Despite his prodigious output, the work of the Mexican dramaturge, playwright, and director Héctor Mendoza has been little studied academically. Those who have examined his works have dismissed his adaptations as merely playing with staging techniques while attempting to remain true to the adapted works' "essence." However, a close examination of one of these adaptations, La dama boba (1981), reveals that Mendoza draws on Spanish Golden Age theater to comment on contemporary issues facing Mexican theater and masculinity. In this paper, I engage with Richard Hornby's varieties of "metadrama" and Judith Butler's notions of gender performativity and citationality to argue that Mendoza employs metatheatrical techniques in order to contribute simultaneously to a postmodern questioning of the notion of the "author" and a destabilization and dismissal of the hegemonic Mexican masculine ideal of the macho .